NOTE ON SULFUR REMOVAL WITH METALLIC COPPER - Jin M.; Xia Ya.; Lei T.; Ma S.; Qiu Ju.; Zhang R. (My University, 2007)
Elemental sulfur is extensively distributed in sediments and soils, whose concentration depends on the origin of the sediments and can be as high as several percent. Furthermore, sulfur is readily dissolved in most common organic solvents during extraction of organic matter from sediments and soils, interfering significantly in gas chromatography–mass spectrometry (GC–MS) or gas chromatography–electron-capture detectors.
Keywords: POLYCHLORINATED BIPHENYL; BITUMEN; ENERGY DISPERSIVE SPECTROSCOPY; GEOCHEMISTRY INTERNATIONAL; SUPERCRITICAL FLUID EXTRACTION